Arbuscular mycorrhizal symbiosis alters the expression patterns of three key iron homeostasis genes, ZmNAS1, ZmNAS3, and ZmYS1, in S deprived maize plants - Chorianopoulou, Styliani N.; Saridis, Yiorgos I.; Dimou, Maria; Katinakis, Panagiotis; Bouranis, Dimitris L. (Frontiers in Plant Science, 2015)
Nicotianamine is an essential molecule for Fe homeostasis in plants, its primary precursor is the S-containing compound methionine, and it is biosynthesized by the enzyme family of nicotianamine synthases. In maize, a graminaceous plant that follows Strategy II for Fe uptake, ZmNAS genes can be subgrouped into two classes, according to their roles and tissue specific expression profiles. In roots, the genes of class I provide NA for the production of deoxymugineic acid, which is secreted to the rhizosphere and chelates Fe(III). The Fe(III)-DMA complex is then inserted to the root via a ZmYS1 transporter. The genes of class II provide NA for local translocation and detoxification of Fe in the leaves. Due to the connection between S and Fe homeostasis, S deficiency causes Fe deprivation responses to graminaceous plants and when S is supplied, these responses are inverted. In this study, maize plants were grown in pots with sterile river sand containing FePO4 and were inoculated with the mycorrhizal fungus Rhizophagus irregularis. The plants were grown under S deficient conditions until day 60 from sowing and on that day sulfate was provided to the plants. In order to assess the impact of AM symbiosis on Fe homeostasis, the expression patterns of ZmNAS1, ZmNAS3 (representatives of ZmNAS class I and class II) and ZmYS1 were monitored before and after S supply by means of real time RT-PCR and they were used as indicators of the plant Fe status. In addition, total shoot Fe concentration was determined before and after S supply. AM symbiosis prevented Fe deprivation responses in the S deprived maize plants and iron was possibly provided directly to the mycorrhizal plants through the fungal network. Furthermore, sulfate possibly regulated the expression of all three genes revealing its potential role as signal molecule for Fe homeostasis.